2017
DOI: 10.1007/s10803-017-3070-z
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for Anxiety and Problem Behavior in Children with Autism Spectrum Disorder and Intellectual Disability

Abstract: There is little research on the functional assessment and treatment of anxiety and related problem behavior in children with autism spectrum disorder (ASD), particularly those with intellectual and developmental disability (IDD). In a recent study, we evaluated a multimethod strategy for assessing anxiety in children with ASD and IDD (Am J Intellect Dev Disabil 118:419-434, 2013). In the present study, we developed treatments for the anxiety and associated problem behavior in these same children. A multiple ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 66 publications
3
30
0
Order By: Relevance
“…The current results are in line with previous reports of anxiety in ASD and ID being associated with SIB (Oliver et al 2017, Soke et al 2017, Kerns et al 2015, and the results from Moskowitz et al (2017b) where problem behaviours decreased as anxiety markers decreased in children with ASD and ID. These findings highlight the importance of conducting thorough psychiatric assessment in cases involving ASD, ID and "challenging" behaviours such as SIB.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current results are in line with previous reports of anxiety in ASD and ID being associated with SIB (Oliver et al 2017, Soke et al 2017, Kerns et al 2015, and the results from Moskowitz et al (2017b) where problem behaviours decreased as anxiety markers decreased in children with ASD and ID. These findings highlight the importance of conducting thorough psychiatric assessment in cases involving ASD, ID and "challenging" behaviours such as SIB.…”
Section: Discussionsupporting
confidence: 93%
“…If Philip seemed more agitated, tactile sensory diversions were introduced, such as caregivers taking initiative to kick a ball and get Philip to throw or kick it back, offering Philip a snack or a drink. These strategies are similar to those described as "exposure paired with anti-anxiety stimuli" or "counterconditioning" by Moskowitz et al (2017b) and "anxiety relief" or "grounding" by Bakken et al (2014). "Grounding" in trauma treatment may refer to any technique that aids the patient in re-establishing an awareness of the present (Kennerley, 1996).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study explored the relationship between multidimensional anxiety, alexithymia, dependence and emotional-behavioral problems in adolescents. Consistent with previous studies, adolescents with anxiety symptoms have shown increased emotional-behavioral problems [45][46][47][48], and multidimensional anxiety. Negative personalities are positive predictors of adolescent emotional-behavioral problems [22].…”
Section: Discussionsupporting
confidence: 88%
“…In other studies were researched functional treatments of anxiety processes Moskowitz et al [6], which, likewise, they start from previous competence development, evaluated from a multiple strategy, as well as, from theoretical base of behaviors as part of the associated global behavior, thoughtful as a multicomponent process, as soon as include different strategies, both individualized positive behavior support skills and cognitive behavioral therapies, encouraging, likewise, as they also affirm Clarke, Hill & Charman [7], the participation of all social factors involved in educational process of children with ASD. These studies move over field of intervention, concluding that exclusively clinical environments must to be replaced for cultural contexts adapted to individual needs, becoming applied programs based on the school and in right context, which allow seeming improvements to happen where exclusively clinical environments don´t find them Drmic, Aljunied & Reaven [8].…”
Section: Introductionmentioning
confidence: 99%